Універсальна методика розрахунку обмоткових коефіцентів - Лущик, В.Д. (Електротехніка і електромеханіка, 2011)
The universal method of winding coefficients calculation is expounded, which is based on the use of imaginaries. A method is extraordinarily simple and allows to calculate the winding coefficients of any winding without an exception. Some publications of the last years which are devoted the calculations of winding coefficients are considered.